Towards a parameter-free theory for electrochemical process at the nano-scale - KUMAR, ASHWINEE (Trinity College Dublin. School of Physics. Discipline of Physics, 2019)
The mass and charge distribution at electrochemical interfaces plays a key role in driving electrochemical phenomena. However, in spite of its importance, even the structure of the Pt/water interface under bias, the most basic electrochemical interface, is still almost entirely unknown. Here we present the first ab initio simulation of the double layer structure at the Pt/water interface in realistic solution conditions and its dependence on an applied potential. Our results are enabled by a newly developed ab initio charging approach, which is here briefly described. We reveal that the double layer structure, number density and charge distribution, strongly depends on the applied potential. Furthermore, we show that the metal/surface charging state cannot be described using a traditional simple capacitor model. In fact, the interfacial dipole is not merely determined by the reorientation of the first water layer in contact with the metal surface, but also by its charging state in combination with its number density. Water reorientation becomes relevant only in the second water layer. The dependence of the structure of the Pt/water double layer on the applied potential will likely affect the catalytic processes therein.
APPROVED
Keywords: modelling bias; modelling of interface; computational electrochemistry; Pt-water interface; Ag-water interface; ab initio MD; DFT; CP2K; parameter free theory; electrochemical process; nanoscale